Frequently asked questions about the ancient Olympic Games
Frequently Asked Questions about the Ancient Olympic Games 1.Where did the Olympic games come from? 2.Why were they held at Olympia? 3.Were there other contests like the Olympics? 4.Who could compete in the Olympics? 5.Were women allowed at the Olympics? 6.How were the athletes trained? 7.What prizes did Olympic victors get? 8.Who were the Olympic judges? 9.What was the penalty for cheating? 10.Where did the marathon come from?